(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2021)
Cosmetic and skin care industry has evolved dramatically in the recent years. There are enormous brands of such products in which the hair coloring and henna products are considered the most common product used widely within Libya market by both males and females. This paper discusses the lead (Pb) content in six hair coloring and henna brands and their effect on hair and human body. The results showed concentration range < 0.005-3.043 µg/g. The upper lead content is detected in Compagnia Del hair color brand and the lowest lead content is detected in Royal henna all results were within the permissible limits 20 µg/g.